2017
DOI: 10.3832/ifor2078-009
|View full text |Cite
|
Sign up to set email alerts
|

Comparing land use registry and sample based inventory to estimate forest area in Podlaskie, Poland

Abstract: The Land and Property Register (LPR) of Poland contains information on land use for the entire country. Additionally, a sample-based National Forest Inventory (NFI) provides statistical data for forest areas and detailed information on numerous forest parameters. However, until 2014 NFI plots were established only on areas classified as forest in the LPR. In this article, we present results of an estimation of forest area by extending the NFI measurements on all theoretical points in a grid, and compare the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…This was confirmed in a study by Hościło et al [71] based on spatial databases, which showed that Poland's forest cover was already 32% in 2014, and the actual forest area was almost 800 kha larger than that published by Statistics Poland. A study by Jablonski et al [72] conducted in the Podlaskie Voivodeship indicate similar discrepancies (about 2.4 percentage points more than the public data). The main reasons for the mentioned differences are the spontaneous appearance of trees on abandoned agricultural land [73] and, especially, the aforementioned delays in the reclassification of afforestation into forest land.…”
Section: Problems In Data Comparabilitymentioning
confidence: 72%
“…This was confirmed in a study by Hościło et al [71] based on spatial databases, which showed that Poland's forest cover was already 32% in 2014, and the actual forest area was almost 800 kha larger than that published by Statistics Poland. A study by Jablonski et al [72] conducted in the Podlaskie Voivodeship indicate similar discrepancies (about 2.4 percentage points more than the public data). The main reasons for the mentioned differences are the spontaneous appearance of trees on abandoned agricultural land [73] and, especially, the aforementioned delays in the reclassification of afforestation into forest land.…”
Section: Problems In Data Comparabilitymentioning
confidence: 72%
“…Comparing the above data with the increase in area (566 thousand hectares), it should be noted that 231 thousand hectares of forest were created by activities other than those mentioned above. This is primarily due to the organization of the Land and Property Register, i.e., the reclassification of areas that were afforested in previous years and were not listed in the official register, as well as areas that became covered with forest vegetation as a result of natural succession [33,62].…”
Section: Forecasts Of the Increase In Forest Area In Polandmentioning
confidence: 99%
“…Reporting of forest area in Poland is based on data published in the statistical yearbooks "Forestry" and "Environmental Protection" of the Central Statistical Office. Details of the definition of forest area formulated for Poland in the Forest Act (Act on Forests, 1991), FAO/UN [9][10][11] and the Kyoto Protocol [12] are presented in Table 2 [13][14][15][16]. The definition of forest in the 1991 Forestry Act (in Poland) does not require canopy cover or height.…”
Section: Introductionmentioning
confidence: 99%
“…Areas with or without forest vegetation may be also excluded or included in the forest area due to their land use. Moreover, there are many such rules that result in the forest area, which varies according to the definition used [13][14][15][16]. Ultimately, different forest areas are reported even for a single country.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation